2014
DOI: 10.4236/fns.2014.519199
|View full text |Cite
|
Sign up to set email alerts
|

Sensory Analyses and Nutritional Qualities of Hand-Made Breads with Organic Grown Wheat Bread Populations

Abstract: Population varieties can meet the needs of organic farming as they are composed of diverse genotypes and have nutritional and sensory characteristics of interest. Their intra-specific genetic variability helps to adapt to the diversity of soil and climate conditions, management practices and needs. Moreover, an integrated organic bread sector has emerged willing to use more wheat populations. To explore sensory and nutritional potential of bread wheat populations, hedonic tests, sensory profile and nutritional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 24 publications
2
9
0
1
Order By: Relevance
“…The model below, similar to that used by Vindras-Fouillet et al (2014), incorporated the effects of variety, panelist, order and their subsequent interactions. A reduced model was used if there was not a second replicate (e.g., sensory evaluation of cooked grain) or an order term (e.g., baking trials).…”
Section: Discussionmentioning
confidence: 99%
“…The model below, similar to that used by Vindras-Fouillet et al (2014), incorporated the effects of variety, panelist, order and their subsequent interactions. A reduced model was used if there was not a second replicate (e.g., sensory evaluation of cooked grain) or an order term (e.g., baking trials).…”
Section: Discussionmentioning
confidence: 99%
“…The colour of the wheat bran (red or white) may also affect palatability of products made from the wheat. A French study showed that consumers there preferred the taste of red wheat cultivars (Vindras-Fouillet et al 2014). In Norway, all spring wheat cultivars are red since white cultivars have a higher risk of pre-harvest sprouting, which is an important negative characteristic with Norwegian climatic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The first one searches for quality indicators by crossing physico-chemical data or genetic data with sensory ones [30], [31]. The second trend searches for adapting sensory methodologies to specific context such as the postharvest assessment of sensory properties of fruit or the sensory evaluation of wine with professional [32], [33], [34]. In the farmers-bakers sector, real relationship occurred between consumers and farmers, consumers buy the farmers' bread and not a bread from a farmer.…”
Section: Overall Discussion: Confronting Breeding Strategies With Fiementioning
confidence: 99%